Conocimiento y aceptación de la afiliación voluntaria a la seguridad social de las amas de casa en el cantón Loja - Arias Cordero, Janeth Yesenia (2016)
The research aims to determine the degree of knowledge and acceptance of voluntary affiliation to social security by housewives in the canton Loja, to do a diagnosis of the current knowledge possessed by the beneficiaries of the initiative implemented is by the Ecuadorian Institute of social Security, as is the supply of personal, social and economic benefits, in addition to the legal requirements and gain; also ranges to calculate the amount of contribution, as well as contingencies not covered. All this thanks to information obtained from the perception of officials of the Ecuadorian Institute of Social Security, literature review and the opinion of the housewives of Canton Loja (beneficiaries of the initiative). In analyzing the qualitative and quantitative information collected, it is determined that the lack of promotional campaigns by the Ecuadorian Institute of Social Security in terms of the services offered by it, as well as economic and legal benefits, coverage, important data, etc. it brings the initiative of voluntary social security of housewives affiliation; It has generated insecurity beneficiary of this initiative, since not possess adequate information (47.46%), the acceptance of it will be challenged in a 86.58%.